2011
DOI: 10.1007/s13204-011-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of Chromium (VI) from wastewater using nanomaterials like TiO2, ZnO, and CdS

Abstract: The photocatalytic degradation of Cr(VI) from wastewater by using nanomaterials TiO 2 , ZnO, and CdS. All the experiments were carried out in the batch process. The wastewater obtained from various industries. The amount of chromium was removed using photocatalyst with UV light and in the dark at different pH range. The maximum removal of Cr(VI) was observed at pH 2; out of these photocatalyst TiO 2 showed highest capacity for Cr(VI) removal than TiO 2 thin film. The removal of chromium has been studied by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 20 publications
(21 reference statements)
1
24
0
Order By: Relevance
“…This can lead to redox reactions with adsorbed species such as water, hydroxide ions (OH À ), organic compounds, or oxygen to generate free radicals. 9,11 TiO 2 particulates have also been utilised as sunscreens as they are able to reect and scatter the UVA and UVB component of sunlight. Although the average size of the titania particles used in such formulations are primarily in the micrometre range, such polydisperse materials usually contain a certain fraction of nano-sized titania particles.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to redox reactions with adsorbed species such as water, hydroxide ions (OH À ), organic compounds, or oxygen to generate free radicals. 9,11 TiO 2 particulates have also been utilised as sunscreens as they are able to reect and scatter the UVA and UVB component of sunlight. Although the average size of the titania particles used in such formulations are primarily in the micrometre range, such polydisperse materials usually contain a certain fraction of nano-sized titania particles.…”
Section: Introductionmentioning
confidence: 99%
“…Humic substance have high molecular weight naturally occurring in yellow-brown, by using TiO 2 80% humic acid reduction is reported ( Liu et al ., 2008 ), in another paper 65% reduction in humic acid reported ( Valencia et al ., 2018 ) In organic pollutant present in waste water in the form of nitrates, halides, ammonia, cyanide and thiocyanate these pollutant an effectively decompose by photocatalytic process. Different semiconductors nanoparticles such as TiO 2 against AgNO 3 , TiO ( López-Muñoz et al, 2016 , Hong et al, 2009 ) ZnO against Cr(Vi) and potassium cyanides ( Joshi and Shrivastava, 2011 , Bagabas et al, 2013 ) and CdS/Titanate nanotubes reported against ammonia in water ( Lee et al ., 2002 ).…”
Section: Application Of Photo-catalystmentioning
confidence: 99%
“…The chromium was removed using photocatalyst with UV light and in the gloomy at diverse pH range. The utmost removal of Cr(VI) was pragmatic in pH 2 and TiO 2 showed peak ability for Cr(VI) removal than TiO 2 thin film [24]. To the best of our knowledge, there are no reports on the structured nanoporous facile Fe 2 O 3 and its impact on the photocatalytic degradation of chromium (VI) under visible light.…”
Section: Introductionmentioning
confidence: 99%